2006
DOI: 10.1158/1535-7163.mct-06-0111
|View full text |Cite
|
Sign up to set email alerts
|

Activity of PXD101, a histone deacetylase inhibitor, in preclinical ovarian cancer studies

Abstract: Histone deacetylase inhibitors represent a promising new class of anticancer agents. In the current investigation, we examined the activity of PXD101, a potent histone deacetylase inhibitor, used alone or in combination with clinically relevant chemotherapeutics (docetaxel, paclitaxel, and carboplatin), in preclinical in vitro and in vivo models of ovarian cancer. In vitro activity was examined in ovarian cancer and multidrug-resistant cell lines grown in monolayer culture, and in primary clinical ovarian canc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 36 publications
(37 reference statements)
5
93
1
Order By: Relevance
“…It has been reported previously that hydroxamic acid-based inhibitors such as belinostat, are potent inducers of differentiation and/or apoptosis in transformed cells in culture including prostate cancer cells (10,28,29). Here we confirm that Belinostat, a member of hydroxamic acid-based inhibitors, suppresses, in vitro and in vivo, the growth of a wide panel of prostate tumor cells with graded androgen dependence at micromolar concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported previously that hydroxamic acid-based inhibitors such as belinostat, are potent inducers of differentiation and/or apoptosis in transformed cells in culture including prostate cancer cells (10,28,29). Here we confirm that Belinostat, a member of hydroxamic acid-based inhibitors, suppresses, in vitro and in vivo, the growth of a wide panel of prostate tumor cells with graded androgen dependence at micromolar concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…30,[59][60][61][62][63][64][65][66][67][68] Belinostat has been found to be synergistic with taxanes in inducing apoptosis in prostate and ovarian cell lines and in clinical samples from ovarian tumors grown in organoid culture. 65,67 Although most of these studies did not explore mechanism, cytotoxicity induced by vorinostat and paclitaxel in breast cancer cell lines was accompanied by increased induction of G2/M arrest. 62 A study of Hela cells showed that combining the hydroxamate HDACi, trichostatin A, with paclitaxel disrupted the association of BubR1 with kinetochores and reduced clonogenic survival.…”
Section: Discussionmentioning
confidence: 99%
“…These results are summarised in table 3. The exposure following oral dosing of belinostat was variable but sufficient to achieve histone acetylation ( Figure 2) and in a potentially therapeutic range based on observations in pre-clinical models [8][9][10]. Total mean daily AUC of 2767 1453 ng hr/ml (8.7 4.6 M hr) resulted from a dose of 1000 mg/m 2 once daily (qd).…”
Section: Pharmacokineticsmentioning
confidence: 99%